Fluorescent diagnostics of non-melanoma skin cancer - E. V. Filonenko; V. I. Ivanova-Radkevich (Biomedical Photonics)
Fluorescent diagnostics is a promising method for diagnosing non-melanocytic skin tumors, which makes it possible to identify clinically undetectable skin cancer foci and clarify the margin of the tumor lesion. The main drugs for fluorescent diagnostics are drugs based on 5-aminolevulinic acid and its methyl ester. Sensitivity indicators of fluorescent diagnostics in basal cell, squamous cell carcinoma and extramammary Paget’s disease reach 79.0-100.0%, speci city – 55.6-100%. But the effectiveness of this method may be reduced due to hyperkeratinization, keratinization, and the presence of necrotic tissue on the surface of tumor foci. Comparative studies of the results of fluorescent diagnostics and histological mapping during tumor removal using Mohs micrographic surgery showed approximately equal results in the determining of the tumor edges by these methods, which indicates that safe and technically easily performed fluorescent diagnostics can serve as a good alternative to Mohs micrographic surgery, one of the most accurate, but rather labor-intensive and technically complex method for determining the margin of skin cancer foci.